E-130 Step forward: early experience using OCT technology in neurovascular field. (4th August 2020) - Mejia, J; Gutierrez, J; Patino Hoyos, M; Torres, V; Pabon Guerrero, B
Abstract : Introduction: Optical Coherence Tomography (OCT) is a validated technology in cardiac and peripheral vasculature. However, it uses for neurovascular procedures only have been described in few publications of animal lab, cadaveric models and some case reports. Detection of high-resolution (micron-scale) findings intra-procedural and during follow-up in the treatment of variety of Neurovascular conditions are described bellow. Methods: Since introduction of this technology in our institution 2018, after learning curve was acquired and IRB approved INR application, we retrospectively described the OCT use to evaluate Intra and extra cranially device implanted. Clinical, anatomical, angiographic variables were registered. Devices such as monolayer and dual-layer flow diverter stents, monolayer and dual-layer carotid stents, and endosaccular flow disruption devices such as the WEB device, were evaluated using this technology. Results: A total of 6 patients were selected to be evaluated using OCT. Eleven Dragonfly Otis Imaging Catheters (Abbott Vascular), assisted with the use of a triaxial system as support were registered. All cases performed under GA and full heparinization. Informed consent obtained. OCT evaluation was performed immediately after the procedure, and in 3 and 6 months as follow-up. Description of multiple endovascular findings in the short and mid-term follow-up were determined, such as wall- apposition, device conformability, presence or not of thrombus device-related, atheroma plaque fragmentation or stabilization, fibrin bridges formation processes, neoendothelization and healing process. Additional information was obtained: aneurismal neck permeability, patency of perforators or arterial ostia, which were clearly elucidated in a close-by histologic scale. In the analysis of the WEB device, none evidence of thrombosis, even none material at the radiopaque-proximal marker, findings in the proximal recess, were revealed. No procedural related complications were reported. Conclusion: Intravascular OCT technology may be suitable to use in Neurovascular procedures highly selected. In our experience an accurate training and learning curve are mandatory. Under special circumstances the use of OCT for INR showed to be feasible and safe. The valuable information acquired still is under analysis but constitutes an extra tool to evaluate intraprocedural results and to assess the healing process during the follow up. Disclosures: J. Mejia: None. J. Gutierrez: None. M. Patino Hoyos: None. V. Torres: None. B. Pabon Guerrero: None.